1993
DOI: 10.1080/07391102.1993.10508695
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Thermostability and Structure of Close Homologues - Barnase and Binase

Abstract: Parameters of heat denaturation and intrinsic fluorescence of barnase and its close homologue, binase in the pH region 2-6 have been determined. The barnase heat denaturation (pH 2.8-5.5) proceeds according to the "all-or-none" principle. Barnase denaturation temperature is lower than that of binase and this difference increases from 2.5 degrees C at pH 5 to 7 degrees C at pH 3. Enthalpy values of barnase and binase denaturation coincide only at pH 4.5-5.5, but as far as pH decreases the barnase denaturation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 16 publications
3
37
0
2
Order By: Relevance
“…3). This value is somewhat larger than reported by Makarov et al (1993), 3.8 kJ K-I mol", but is in good correspondence with the denaturation heat capacity increment determined directly from the calorimetrically recorded heat capacity function at T, = 50 "C, the averaged value of which is 5.7 kJ K" mol" ( Table 2). The difference between the heat capacities of the native and dena- tured states depends on temperature (Fig.…”
Section: The Enthalpy Of Barnase Unfoldingsupporting
confidence: 86%
See 4 more Smart Citations
“…3). This value is somewhat larger than reported by Makarov et al (1993), 3.8 kJ K-I mol", but is in good correspondence with the denaturation heat capacity increment determined directly from the calorimetrically recorded heat capacity function at T, = 50 "C, the averaged value of which is 5.7 kJ K" mol" ( Table 2). The difference between the heat capacities of the native and dena- tured states depends on temperature (Fig.…”
Section: The Enthalpy Of Barnase Unfoldingsupporting
confidence: 86%
“…In solutions close to neutral pH, reversible unfolding of barnase by denaturants and temperature appears to be a 2-state transition (Hartley, 1968(Hartley, , 1975Makarov et al, 1993). Our earlier unpublished calorimetric studies of the heat denaturation of barnase, carried out at the Protein Research Institute in Russia in 1989, showed also that this process is approximated well by a 2-state transition.…”
mentioning
confidence: 90%
See 3 more Smart Citations